BAY 1125976, a selective allosteric AKT1/2 inhibitor, exhibits high efficacy on AKT signaling‐dependent tumor growth in mouse models. Issue 2 (20th October 2016) - Politz, Oliver; Siegel, Franziska; Bärfacker, Lars; Bömer, Ulf; Hägebarth, Andrea; Scott, William J.; Michels, Martin; Ince, Stuart; Neuhaus, Roland; Meyer, Kirstin; Fernández‐Montalván, Amaury Ernesto; Liu, Ningshu; et al.
Abstract : The PI3K‐AKT‐mTOR signaling cascade is activated in the majority of human cancers, and its activation also plays a key role in resistance to chemo and targeted therapeutics. In particular, in both breast and prostate cancer, increased AKT pathway activity is associated with cancer progression, treatment resistance and poor disease outcome. Here, we evaluated the activity of a novel allosteric AKT1/2 inhibitor, BAY 1125976, in biochemical, cellular mechanistic, functional and in vivo efficacy studies in a variety of tumor models. In in vitro kinase activity assays, BAY 1125976 potently and selectively inhibited the activity of full‐length AKT1 and AKT2 by binding into an allosteric binding pocket formed by kinase and PH domain. In accordance with this proposed allosteric binding mode, BAY 1125976 bound to inactive AKT1 and inhibited T308 phosphorylation by PDK1, while the activity of truncated AKT proteins lacking the pleckstrin homology domain was not inhibited. In vitro, BAY 1125976 inhibited cell proliferation in a broad panel of human cancer cell lines. Particularly high activity was observed in breast and prostate cancer cell lines expressing estrogen or androgen receptors. Furthermore, BAY 1125976 exhibited strong in vivo efficacy in both cell line and patient‐derived xenograft models such as the KPL4 breast cancer model (PIK3CA H1074R mutant), the MCF7 and HBCx‐2 breast cancer models and the AKT E17K mutant driven prostate cancer (LAPC‐4) and anal cancer (AXF 984) models. These findings indicate that BAY 1125976 is a potent and highly selective allosteric AKT1/2 inhibitor that targets tumors displaying PI3K/AKT/mTOR pathway activation, providing opportunities for the clinical development of new, effective treatments. Abstract : What's new? AKT is a critical kinase implicated in controlling the development of cancer and the resistance to cancer treatments. Here a group of authors from the company Bayer report that a novel allosteric AKT1/2 inhibitor developed by the company (BAY 1125976) inhibits the proliferation of several human cancer cell lines and demonstrates in vivo antitumor activity in cell line and patient‐derived xenograft models. These results make BAY1125976 a promising new anti‐cancer candidate drug and underscore the clinical relevance of AKT inhibitors in the treatment of cancers with pronounced AKT signaling.